Experimental investigation of air-conditioning electrical compressor using binary TiO2–SiO2 polyol-ester nanolubricants - Mohd Anwar, Zawawi; Wan Hamzah, Wan Azmi; Khamisah, Abdul Hamid; Hendrawati, T. Y.; Muhammad Aminullah, Abdul Rahman (Elsevier Ltd, 2024)
As electric vehicles (EVs) continue to replace conventional gasoline vehicles, maintaining thermal comfort within the car requires additional energy to operate the automotive air-conditioning (AAC) system. This work aims to optimise the electrically driven compressor (EDC) system utilising polyol-ester (POE)-based binary nanolubricants to enhance performance and minimise the size of the EV battery and AAC components. A binary nanolubricant was formulated using a two-step method of formulation. The TiO2–SiO2/POE binary nanolubricant was prepared at different volume concentrations ranging from 0.01 to 0.1 %. The experiment was conducted for the 1200–3840 rpm compressor speed with different initial refrigerant charges between 120 and 160 g. The heat absorption rose by up to 44.2 % while utilising the binary nanolubricant at a volume concentration of 0.03 %. The coefficient of performance (COP) reached its maximum value of 2.43 at a refrigerant charge of 160 g and compressor speed of 1860 rpm. Furthermore, the binary nanolubricant significantly reduced the expansion valve discharge temperature, exhibiting a substantial decrease of up to 51.6 %. The highest COP increment, up to 23.4 %, was achieved at a volume concentration of 0.03 %. Hence, it is recommended to utilise 0.03 % TiO2–SiO2/POE binary nanolubricant to achieve optimal performance in the AAC-EDC system.